Persepsi Siswa Terhadap Layanan Tenaga Administrasi Sekolah Di Sekolah Menengah Kejuruan (SMK) Teknik Negeri Se-Kota Padang - Nadya Mahwadah Tiffani; Jasrial Jasrial; Nurhizrah Gistituati; Yulianto Santoso (Universitas Negeri Padang, 2021)
This study is to get a sketch of Student Perceptions of School Administrative Personnel Services. This assessment is descriptive quantitative in nature. The population in this study were 870 students of State Technical Vocational High Schools in Padang City. Sampling in this study is proportional random sampling obtained by 84 students. The assessment instrument carried out was in the form of a questionnaire on a linkert scale. This questionnaire has been tested to see its validity and reliability. The results of this study prove that the students' perceptions of the service of school administrative personnel in technical vocational high schools (SMK) in the city of Padang: 1) observed from the timeliness of the assessment by category enough to get an average score of 3.06, 2) the aspect of hospitality with a sufficient category by getting an average score of 3.13, 3) observed from the aspect of responsibility with a sufficient category by getting an average score of 3.03, 4) observed from the aspect of the procurement of supporting facilities with a sufficient category to get an average score - Average 3.33, 5) observed from the aspects that get service with enough category get an average score of 3.13, and 6) observed from the aspect of comfort who get service with enough category get an average score of 3.30. This examination was denied that the Students' Perceptions of School Administration Personnel Services in the State Technical Vocational School (SMK) Padanf City with a sufficient category got an average score of 3.16. Suggestions that can be given are that efforts are needed to improve Student Perceptions of School Administration Personnel Services to be even better.